2018
DOI: 10.1007/s10943-018-0563-9
|View full text |Cite
|
Sign up to set email alerts
|

Leading God’s People: Perceptions of Influence Among African–American Pastors

Abstract: Religious leaders, particularly African-American pastors, are believed to play a key role in addressing health disparities. Despite the role African-American pastors may play in improving health, there is limited research on pastoral influence. The purpose of this study was to examine African-American pastors' perceptions of their influence in their churches and communities. In-depth interviews were conducted with 30 African-American pastors and analyzed using a grounded theory approach. Three themes emerged: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Data from the interviews suggest that targeting the health practices of church leaders would be a key strategy that would facilitate implementation and sustainment of health promotion programs in churches. In all religious denominations, pastors are role models and play a critical role in defining the characteristics of church life [73,74]. Maton found that church groups with capable leaders reported positive group assessments and well-being, and that pastors influence attendees' commitment and perceived social support [75].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the interviews suggest that targeting the health practices of church leaders would be a key strategy that would facilitate implementation and sustainment of health promotion programs in churches. In all religious denominations, pastors are role models and play a critical role in defining the characteristics of church life [73,74]. Maton found that church groups with capable leaders reported positive group assessments and well-being, and that pastors influence attendees' commitment and perceived social support [75].…”
Section: Discussionmentioning
confidence: 99%
“…In all religious denominations, pastors are role models and play a critical role in defining the characteristics of church life. 74,75 Maton found that church groups with capable leaders reported positive group assessments and well-being, and that pastors influence attendees' commitment and perceived social support. 76 Increasing the self-efficacy of leaders to engage in PA and providing education on the benefits of PA could empower leaders to promote PA and create wellness policies in their congregation.…”
Section: Discussionmentioning
confidence: 99%
“…In all religious denominations, pastors are role models and play a critical role in defining the characteristics of church life. 64,65 Maton found that church groups with capable leaders reported positive group assessments and well-being and that pastors influence attendees' commitment and perceived social support. 66 Increasing the self-efficacy of leaders to engage in PA and providing education on the benefits of PA could empower leaders to promote PA and create wellness policies in their congregation.…”
Section: Discussionmentioning
confidence: 99%